Dynamic Cryptographic Algorithm to Provide Password Authentication using Cued Click Points - P. Ashok (Institute of Advanced Engineering and Science, 2017)
Nowadays, password based authentication is one the most common way of authentication for most of the user logins. However, the advancement in technology also posing many threats for the password authentication systems. Everybody will be keen to know others password. But there exists a very few who is very keen to devise a new authentication. In this paper, we have proposed a more advanced password authentication method yet a simple one which gives a tough competition for the attacker to break the password. For this, we are providing a special key-display interface to assist the modified cued click point’s technique which helps in the more sophisticated dynamic authentication method. This interface helps to break the single password into a combination of 4 passwords and also adds three more password strings to the current password which is entered. It also uses a special one way encryption algorithm called Nesting 93 which is developed explicitly for this system. It helps to prevent almost any kind of attacks.